AN ASSESSMENT OF THE IMPACT OF IECC ON ELECTRICITY CONSUMPTION IN RESIDENTIAL BUILDINGS OF LAHORE, PAKISTAN - Shakeel, Asma (European Scientific Journal, ESJ, 2013)
Energy consumption in residential sector is the highest among all sectors in Pakistan. Therefore Buildings Energy Conservation Codes (BECC) can serve as a strategy to ensure energy saving by designing energy efficient buildings. The objective of this research is to assess the impact of U-Value in international energy conservation codes (IECC) with regard to design of energy efficient residential buildings for middle income families in Lahore. The present research will also focus on developing an assessment process using these international standards as benchmark in order to address the local conditions set by climatic studies, and their application on the design requirements of the residential buildings. In order to assess the impact of IECC on the consumption of electricity in residential building for middle income families of Lahore, an existing house in Lahore was selected as a base case. A comparative analysis of the electricity consumption was done using the base case of commonly used envelope materials and three proposed cases of locally available materials which are closest possible to reference standards of IECC. The comparison of results shows that up to 39 % of electricity is possible to be saved by applying the standards as suggested in IECC. The results will help in designing the energy efficient residential buildings in future.